WIATEC - a world integrated assessment model of global trade environment and climate change - Truong Phuoc Truong; Claudia Kemfert (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper describes the structure of the World Integrated Assessment model of global Trade, Environmental, and Climate change (WIATEC).The model consists of a multi-regional multi-sectoral core CGE model linked to a climate model. The core CGE is based on an existing global trade and environment model called GTAP-E (Truong, 1999; Burniaux and Truong, 2002). A suite of different and interchangeable 'modules' are then built around this 'core' to enable the model to be able to handle a range of different policy issues such as CO2 emissions, abatement, trading, non-CO2 (CH4 and N2O) emissions, land use land use change and forestry (LULUCF) activities, and changing technologies in the electricity generation sector. The approach which uses a core model structure with different additional modules built around this core structure allows the overall model to be flexible and can be adapted to a range of different policy issues. We illustrate the usefulness of this approach in a policy experiment which looks at the interaction between emissions trading scheme and the promotion of renewable energy targets in the European Union climate policy.
Keywords: Q55; O38; C68; 330; Integrated Assessment Model; Technological Change; Climate Policy